2019
DOI: 10.1093/ehjci/jez065
|View full text |Cite
|
Sign up to set email alerts
|

Aortic growth rates are not increased in Turner syndrome—a prospective CMR study

Abstract: Background Aortic disease is a key determinant of outcomes in Turner syndrome (TS). The present study characterized aortic growth rates and outcomes over nearly a decade in adult women with TS. Methods and results Prospective observational study assessing aortic diameters twice with cardiovascular magnetic resonance imaging in women with TS [N = 91; mean follow-up 8.8 ± 3.3 (range 1.6–12.6) years] and healthy age-matched fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Few longitudinal studies have evaluated the aortic diameter progression in large cohorts of TS patients. Mortensen et al [19] found in 91 patients with TS, that the aortic progression at the level of the Valsalva sinuses and the tubular ascending levels were 0.32-±0.3 mm/y and 0.20-±0.2 mm/y, respectively, after a mean follow-up of 8.8 years. A control population of 37 women was included in the study.…”
Section: Aortic Dilatation and Aortic Dissectionmentioning
confidence: 99%
“…Few longitudinal studies have evaluated the aortic diameter progression in large cohorts of TS patients. Mortensen et al [19] found in 91 patients with TS, that the aortic progression at the level of the Valsalva sinuses and the tubular ascending levels were 0.32-±0.3 mm/y and 0.20-±0.2 mm/y, respectively, after a mean follow-up of 8.8 years. A control population of 37 women was included in the study.…”
Section: Aortic Dilatation and Aortic Dissectionmentioning
confidence: 99%
“…This is currently lacking in the United States (Lin et al, ), but under development as a self‐reporting patient registry (Prakash, Lugo‐Ruiz, et al, ). In addition to outcome data focusing on obstetric and fetal/neonatal morbidity, it will be important to extend ongoing population‐based studies of aortic growth (Mortensen et al, ) to assess whether pregnancy has an effect. A recent prospective follow‐up study showed that aortic growth rates in adult women with Turner syndrome overall are similar to healthy female controls.…”
Section: Fertility and Pregnancymentioning
confidence: 99%
“…However, women with a BAV or repaired coarctation of the aorta appeared to dilate more rapidly. Interestingly, planned aortic root or valve surgery was a considerable cause of morbidity and mortality in this cohort (Mortensen et al, ).…”
Section: Fertility and Pregnancymentioning
confidence: 99%
“…According to the latest clinical practice guidelines for the care of girls and women with TS, bicuspid aortic valve (BAV) is the most common CHD in TS affecting between 14-34% of individuals [1]. Aortic dilatation and aortic dissection, which are both associated with the presence of BAV, are common in TS [5]. The management of these acquired aortic conditions is crucial for the cardiovascular outcome of TS patients [6].…”
Section: Introductionmentioning
confidence: 99%